Technical Staff Training at the Ural Private Mining Plants in the First Part of the XIX Century - L. A. Dashkevitch (Образование и наука)
The paper discusses the level and quality of employees’ technical training at the private factories in the Ural region in the pre-reform period of the XIX century, which appears to be one of the least explored aspects in the history of education. Analyzing the existing data and preserved documents, the author attempts to fill the above gaps and demonstrates the dynamics of the private schools development in the factory settlements of the region, their curricula and the government’s attitude to the issue of the factory serfs’ training. The research findings reveal that despite the government’s resistance the number of educated professionals and technicians was gradu- ally increasing in the first half of the XIX century. It was especially noticeable in the large private factories owned by the Demidovs, Stroganoffs and Vsevolozhskys. In the middle of the century, the expertise and skills of the top and senior managerial and technical staff had met the existing requirements. However, the top managers and factory owners anticipated the forthcoming changes in the personnel policy due to the engineering and industrial development in the last half of the century.